ANALISIS PERAN KELOMPOK WANITA TANI DALAM PENGEMBANGAN USAHATANI SINGKONG SEBAGAI UPAYA PENINGKATAN PENDAPATAN KELUARGA DI DESA MAJALENGKA BANJARNEGARA - Sarno Sarno; Rossi Prabowo (Universitas Wahid Hasyim, 2020)
The purpose of the research is to find out the role of farmer women's groups in cassava farming decision making, analyze the efficiency of production costs, and analyze the amount of income and its contribution to increasing family income. The research was carried out in Majalengka Village, Bawang Subdistrict, Banjarnegara District with the aim of the members of the farmer women's group conducting cassava farming as respondents. The study was conducted using descriptive analysis method. The research data are primary and secondary data obtained through in-depth interviews, field observations and sources of various literature literature. The results showed that the average income earned by members of farmer women's groups from cassava farming activities per one production was Rp 649,900,- the efficiency of cassava farming production costs was obtained at 1.84, which means that the production costs incurred it has been efficient, and cassava farming activities carried out by members of women farmer groups contribute 97.7% of the total household income and 2.3% of the income obtained from other businesses. It turned out that cassava farming is very helpful in meeting the household needs of members of the Majalengka village peasant women's group because it is the main occupation. Keywords: Group, Women Farmers, Farming, Cassava, Income